Does the world have low-carbon bioenergy potential from the dedicated use of land?. (November 2017) - Searchinger, Timothy D.; Beringer, Tim; Strong, Asa
Abstract: While some studies find no room for the dedicated use of land for bioenergy because of growing food needs, other studies estimate large bioenergy potentials, even at levels greater than total existing human plant harvest. Analyzing this second category of studies, we find they have in various ways counted the carbon benefits of using land for biofuels but ignored the costs. Basic carbon opportunity cost calculations per hectare explain why alternative uses of any available land are likely to do more to hold down climate change. Because we find that solar power can provide at least 100 times more useable energy per hectare on three quarters of the world's land, any "surplus" land could also provide the same energy and mitigate climate 100 times more if 1% were devoted to solar and the rest to carbon storage. Review of large bioenergy potential estimates from recent IAMs shows that they depend on many contingencies for carbon benefits, can impose many biodiversity and food costs, and are more predictions of what bioenergy might be in idealized than plausible, future scenarios. At least at this time, policy should not support bioenergy from energy crops and other dedicated uses of land. Highlights: Large estimates of bioenergy potential repeatedly err by counting benefits of using land but not costs. On 73% of global land, PV produces at least 100 times more useable energy per hectare. PV plus carbon sequestration would generally produce 100 times more mitigation and same energy. BECCS can only provide additional CCS benefits once all fossil fuel emissions are eliminated. Large IAM energy crop estimates are based on idealized global land scenarios not true projections.